Transparency improves concealment in cryptically coloured moths. (14th November 2019) - Arias, Mónica; Elias, Marianne; Andraud, Christine; Berthier, Serge; Gomez, Doris
Abstract: Predation is a ubiquitous and strong selective pressure on living organisms. Transparency is a predation defence widespread in water but rare on land. Some Lepidoptera display transparent patches combined with already cryptic opaque patches. A recent study showed that transparency reduced detectability of aposematic prey with conspicuous patches. However, whether transparency has any effect at reducing detectability of already cryptic prey is still unknown. We conducted field predation experiments with free avian predators where we monitored and compared survival of a fully opaque grey artificial form (cryptic), a form including transparent windows and a wingless artificial butterfly body. Survival of the transparent forms was similar to that of wingless bodies and higher than that of fully opaque forms, suggesting a reduction of detectability conferred by transparency. This is the first evidence that transparency decreases detectability in cryptic terrestrial prey. Future studies should explore the organization of transparent and opaque patches in animals and their interplay on survival, as well as the costs and other potential benefits associated with transparency on land. Abstract : Does wing transparency in cryptically‐coloured butterflies provide increased protection against visuallyhunting predators? We compared survival [or predation] of artificial cryptic prey with and without transparent areas placed on trunks in a natural forest environment and exposed to wild insectivorous birds. We found that transparency enhances survival compared to opaque cryptically‐coloured prey, likely due to increased concealment.